In the name of Mazu: the use of religion by China to intervene in Taiwanese elections - Sher, Chien-Yuan (Foreign policy analysis, 2024)
Foreign policy objectives can be achieved through religious institutions as a form of soft power. However, empirical evidence on this form of soft power is limited. In this study, we provide rigorous empirical evidence of electoral influence through the channel of religious institutions. To test the efficacy of this channel of influence, we study the Chinese government’s attempts to influence Taiwanese elections through religious institutions. By leveraging spatial regression methods, we demonstrate that Mazu temples influence electoral behavior through a localized process. The density of urban Mazu temples in Kaohsiung, Taiwan, which are subject to influence from China, is associated with an increase in vote share for the pro-China party in their neighborhoods. However, the influence on voters in urban and village areas is not homogeneous. In contrast to urban temples, the relationship between village Mazu temples and the electoral results is insignificant.